The influence of motivation and training on employee performance at the regional disaster management agency (BPBD) in pidie regency - Herizal Ridwan; Muhammad Nur; Ismayli Ismayli (Institute of Computer Science (IOCS), 2023)
This research discusses the impact of motivation and training on the performance of the district disaster management agency (BPBD) in Pidie district. The aim of this research is to determine the influence of motivation and training on the performance of the local disaster management agency (BPBD) in Pidie district. By using the method Structural Equation Modelling-Partial Least Square (SEM-PLS), which is divided into two: the outer model (model of measurement) and the inner model (model structural). The results of the analysis found that the factors that affect the performance of employees in the Disaster Management Agency (BPBD) district of Pidie are motivational variables (wages, working conditions, opportunities to advance, success of tasks) and training variables. (Improve skills, useful materials, training variations, staff qualifications and coach qualifications). The study demonstrates that employee performance is positively impacted by training and motivation. The study's findings support the idea that performance may be improved in firms by offering staff good training programs. Training should be the main emphasis of all firms that wish to improve employee performance because it also inspires workers to perform at better levels